SOME FEATURES OF STUDYING SEMANTIC STRUCTURE OF PHRASEOLOGICAL UNITS IN RUSSIAN AND UZBEK (Scientific journal of the Fergana State University, 2023)
The article deals with the comparative study of adverbial phraseological units in Russian and Uzbek